Regulasi Penegakan Hukum terhadap Pencemaran Air di Sungai Citarum, Jawa Barat - Dhita Amelia (Program Studi Ilmu Hukum, Universitas Kuningan, 2024)
The principle of environmental insight is the principle of capital investment carried out while still paying attention to and prioritizing environmental protection and maintenance. The government in carrying out development must also pay attention to the ecosystem and the surrounding environment. The purpose of this study is to analyze and enforce the law on Citarum River pollution based on the Principle of Environmental Insight, which includes the principles of sustainability, community participation, and environmental responsibility. The method used in this study is normative juridical with qualitative analysis with the data produced in the form of secondary data obtained from previous studies, laws and regulations, and other sources. The results of the study are the Regulation on water pollution in Article 60 of the PPLH Law: